Digital Imaging Inspection System for Aluminum Case Grinding Quality Control of Solid-State Drive - Chun-Jen Chen; Cheng-Feng Tsai (Engineering Proceedings)
The enterprise or data center does not use the M2 SATA because of the cooling problem. Therefore, SSDs employ metal cases similar to the traditional 2.5” or 3.5” hard disk. The metal case is made of aluminum, which must be ground after the metal plate forming process. Conventionally, quality control is conducted to check the ground quality of aluminum cases manually. This method is not accurate as the data are difficult to digitize. To improve the quality control, speed, and efficiency. We established a digital imaging-based inspection system for the aluminum case grinding quality control. The inspection system consists of a digital industrial camera, a closed-circuit TV lens, a light-emitting diode (LED) light source, and a personal computer. If the loading and unloading time is ignored, the test time is less than five seconds for one case. When the tested case is uploaded to the inspection system, the camera captures and sends images to the computer. The image was processed to evaluate the quality and record the tested results. Then, the tested case is classified by a robot or an operator.